The Effect of Woolwich Massage on Breast Milk Production in Postpartum Mothers at the Marbau Health Center, Marbau District, Labuhan Batu Utara Regency in 2021 - Sumiatik (Institute of Computer Science (IOCS), 2022)
Woolwich massage has several benefits, including increasing prolactin and oxytocin reflexes (let down reflex), preventing blockage, increasing milk production and preventing inflammation or breast engorgement. Labuhan Batu Utara in 2021. This study uses a pre-experimental design, One Group pre-test and post-test design without a control group, the subject group was observed before intervention. The population in this study were all postpartum mothers in February, namely 15 people, Sampling in this study was carried out by the total sampling method, using the Wilcoxon test. The result of this research is that the production of breast milk before woolwich massage is done on postpartum mothers is less than 11 respondents (73.3%). The majority of breast milk production after woolwich massage was carried out on postpartum mothers was sufficient, namely as many as 10 respondents (66.7%). There is a significant effect between woolwich massage on breast milk production in postpartum mothers at the Marbau Health Center, Marbau District, Labuhan Batu Utara Regency in 2021, with a p value of 0.014 (p <0.05). The conclusion of this study is that there is a significant influence between woolwich massage on breast milk production in postpartum mothers at the Marbau Health Center, Marbau District, Labuhan Batu Utara Regency in 2021. It is recommended for health service institutions that health workers and the community can use woolwich massage as an alternative relaxation method to improve and facilitate milk production